A128: Hierarchical Clustering Methodology for Exploration of Proteomic Profile in Tears: Seeking for Markers of Uveitis Associated With Juvenile Idiopathic Arthritis. Issue 11 (March 2014) - Nekhai, Sergei; Hynes, Alla; Ammosova, Tatiana; Obukhov, Yuri; Gaidar, Ekaterina; Kononov, Anatoly; Dubko, Margarita; Nikitina, Tatiana; Serogodskaia, Elena; Kostik, Mikhail; Kalashnikova, Olga; Masalova, Vera; et al.
Abstract : Background/Purpose: Uveitis often is the only initial clinical manifestation of JIA for years. There are no reliable markers of JIA‐associated uveitis and impossibility to overcome ocular barriers impede diagnosis and treatment leading to blindness. During the last years the number of proteins identified in tears increased from 200 (Herber et al., 2001) of only 17 (Zhou et al., 2003) different molecular weights (MW) to 491 (de Souza et al., 2006) with 80 chemokines, cytokines, and growth factors (Sack et al., 2005). Objective of the study is to reveal protein markers of JIA‐associated uveitis in tears using high‐resolution mass‐spectrometry and hierarchical clustering methodology. Methods: Standard clinical protocol was used to diagnose uveitis and JIA. Tear samples drawn from 17 JIA‐patients with uveitis, 4 JIA‐patients without uveitis, 3 patients with systemic vasculitis, 4 patients with idiopathic uveitis and 3 healthy subjects were analyzed. Tears were collected on a filter paper, digested with trypsin and the peptides were purified on Zip tips. The samples were loaded to nano C18 column attached to Shimadzu nano LC coupled in‐line to LTQ Orbitrap XL tandem mass spectrometer (Thermo Fischer Scientific, GA, USA). The mass spectra of the peptides were detected with a data‐dependent 4‐event scan method (a survey FT‐MS parent scan followed by sequential datadependent FT‐MS/MS scans on the three most abundant peptide ions from the parent scan). Proteins were identified from the mass spectra results with Proteome Discoverer software for protein database search using the International Protein Index (IPI) Human Protein Database (version 1.79). Quantification was conducted using SIEVE. Results: About 3000 proteins were detected in tears. Among those, 236 proteins (MW 7.4–466 kDa) were chosen as candidates for early diagnosis of the JIA‐associated uveitis. Besides the rheumatoid factors RFET12, RF‐IP14, RF‐IP24, cytokines and T‐cell receptor alpha‐chain, we identified anti‐CD40 single‐chain antibody fragment A49, inhibiting protein CD40 which is a member of the TNF‐receptor superfamily, lipocalin‐1 precursor, associated with immune response and prostaglandin synthesis, clusterin inhibiting the cytolytic reaction of complement components, anti‐TNF‐alfa antibody light chain Fab fragment, protein phosphatase, regulatory subunit 15B, which plays a role in cell progression, apoptosis and regulation of membrane receptors and channels, DMBT/8kb.2 protein, which takes part in the interaction of tumor cells and the immune system. Conclusion: The result of our study demonstrates the benefits of high resolution mass‐ spectrometry for analysis and development of molecular signatures which can be used in diagnostics. Hierarchical clustering methodology allowed grouping according to expression profiles and the dendrogram construction procedure revealed clusters of proteins associated with iron metabolism as the most promising markers of JIA‐associated uveitis. Earlier it was shown that induced anterior uveitis in the eyes of rats can be described in terms of proteins drawn from the anterior chamber (Sobn et al., 2000), which result is close to our terms of description.